2011
DOI: 10.1111/j.1365-3059.2011.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure and trichothecene genotypes of Fusarium graminearum isolated from wheat in southern Brazil

Abstract: A sample of 140 Fusarium graminearum isolates from Rio Grande do Sul, Brazil, representing three populations at least 150 km from one another, were examined for trichothecene genotype based on PCR amplification of portions of the Tri3 and Tri12 genes and a species-specific (Fg16F ⁄ R) primer pair. Genetic diversity was assessed in a sample of 103 F. graminearum lineage 7 (F. graminearum sensu stricto) isolates using amplified fragment length polymorphism (AFLP) markers. The 15-ADON genotype was dominant, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
62
2
18

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 45 publications
12
62
2
18
Order By: Relevance
“…No Brasil, a giberela em trigo é causada por espécies do complexo Fusarium graminearum, especialmente F. graminearum sensu stricto (Fgss) (SCOZ et al, 2009;ASTOLFI et al, 2012). Os danos ocasionados por giberela em trigo no Brasil incluem a redução no rendimento e a contaminação com as micotoxinas de desoxinivalenol (DON) e nivalenol (NIV) (CASA et al, 2004;DEL PONTE et al, 2012).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…No Brasil, a giberela em trigo é causada por espécies do complexo Fusarium graminearum, especialmente F. graminearum sensu stricto (Fgss) (SCOZ et al, 2009;ASTOLFI et al, 2012). Os danos ocasionados por giberela em trigo no Brasil incluem a redução no rendimento e a contaminação com as micotoxinas de desoxinivalenol (DON) e nivalenol (NIV) (CASA et al, 2004;DEL PONTE et al, 2012).…”
Section: Introductionunclassified
“…Os danos ocasionados por giberela em trigo no Brasil incluem a redução no rendimento e a contaminação com as micotoxinas de desoxinivalenol (DON) e nivalenol (NIV) (CASA et al, 2004;DEL PONTE et al, 2012). No Sul do Brasil, as populações de Fgss (a dominante, com 90% de frequência em isolamentos) e Fmer têm apresentado consistentemente genótipo tricoteceno15-A(acetil)DON, uma forma acetilada de DON, e NIV, respectivamente, o que sugere que podem produzir diferentes concentrações de DON e nivale nol (SCOZ et al, 2009;ASTOLFI et al, 2012). SPOLTI et al (2012a) , evidenciando que as populações produzem ambas as micotoxinas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Fusarium graminearum species complex (Fg complex) comprises more than a dozen lineages or phylogenetic species (Sarver et al, 2011) and is the main causal agent of Fusarium head blight (FHB) of small grain in Brazil and around the world (Goswami and Kistler, 2005;Astolfi et al, 2012). In the Americas, Fusarium graminearum sensu stricto is the dominant species of the Fg complex associated with head blight of wheat (Alvarez et al, 2011;Schmale et al, 2011;Astolfi et al, 2012).…”
mentioning
confidence: 99%
“…In Argentina, F. graminearum sensu stricto was the only phylogenetic species isolated from wheat in different subregions of the main wheat production area (Ramirez et al 2007;Alvarez et al 2011), but F. meridionale and F. boothii were the most important on maize in the Northwest area of Argentina (Sampietro et al 2011). In Brazil, surveys of FGSC isolates from wheat showed that F. graminearum sensu stricto was the dominant species (Astolfi et al 2012), while F. meridionale represented an 80 % of the isolates from maize kernels in the Central and Southern maize growing regions of Brazil (Tessmann et al 2011). In soybean, a preliminary report showed the presence of three species, F. austroamericanum, F. meridionale and F. cortaderiae in soybean samples from Brazil (Martinelli et al 2004).…”
mentioning
confidence: 99%